Structural, Morphological and Magnetic Properties of Nd and Co co-doped BiFeO3 Ceramics at Room temperature (Journal of Bangladesh Academy of Sciences, 2017)
Synthesis and characterization of BiFeO3 samples, co-doped with rare earth Nd and Co in place of Bi and Fe respectively were investigated at room temperature (RT). The formula of the four samples are Co-doped BiFe1xCoxO3 (x = 0.05-0.10) and Nd and Co co-substituted Bi0.95Nd0.05Fe0.95Co0.05O3 and Bi0.90Nd0.10Fe0.90Co0.10O3. These ceramic samples were synthesized by conventional solid state reaction method. The X-ray diffraction patterns clearly reveal that the secondary impurity phases were eliminated significantly due to the simultaneous substitution of Nd and Co in place of Bi and Fe respectively of BiFeO3 ceramics. The surface morphology of the synthesized samples was found to improve due to the simultaneous substitution of Nd and Co in place of Bi and Fe in BiFeO3. The average grain size of the first sample with 5% doping of Co in place of Fe was 1.5?m. In the second sample with 10% Co doping in place of Fe, the average grain size became 1.25 ?m. In presence of 5% Nd in place of Bi as well as with 5% doping of Co in place of Fe , grain size reduced to 0.75?m. The sample with 10% doping of Nd and Co in place of Bi and Fe respectively, average grain size decreased to 0.5?m. The EDX spectroscpoy ensured the presence of Bi, Nd, Fe, Co and O in these samples and their percentage of mass and atoms. Magnetic properties of the samples were also investigated at room temperature by measuring magnetization versus magnetic field (M-H) hysteresis loops. The wider loop clearly demonstrates the significant improvement of the magnetic behavior in 10% Nd and Co doped Bi0.90Nd0.10Fe0.90Co0.10O3 sample. The enhanced magnetic properties might be attributed to the substitution induced suppression of spiral spin structure of BiFeO3. The outcome of this investigation suggests the potentiality of the simultaneous doping of Nd and Co in BiFeO3 ceramics to improve their structural, morphological and magnetic characteristics.Journal of Bangladesh Academy of Sciences, Vol. 41, No. 1, 85-93, 2017